Exposure to video display terminals and risk of small-for-gestational-age birth. - Parazzini F; Chiaffarino F; Chatenoud L; Cipriani S; Ricci E; Chiantera V; Bortolus R; Maffioletti C (Journal of Environmental Health, 2010)
In this study, the authors analyzed the association between video display terminal (VDT) use before and during the three trimesters of pregnancy and risk of small-for-gestational-age (SGA) birth in a case-control study. The cases for this study were 555 women who delivered SGA births. The controls were 1,966 women who gave birth at term to healthy infants of normal weight. In terms of the length of exposure, the odds ratios (OR) of SGA birth were 1.2 for less than one hour and 1.3 for between two and 20 hours per week. For higher usage (more than 20 hours per week), the OR was 1.2 (95% CI: [Confidence Interval] 0.9-1.7). The authors conclude that this study does not show any association between VDT use and risk of SGA birth.